Gynaecological Malignancies Updates and Advances - Yaw Ho, Gwo; Frentzas, Sophia (IntechOpen, 2020)
"Gynaecological Malignancies - Updates and Advances" aims to present a review of the significant advances in the understanding and management of gynaecological malignancies. Major areas of importance in this field will be covered, incorporating new knowledge that has arisen due to the advancements in molecular techniques and the ability to correlate these molecular changes with clinical behaviour of gynaecologic tumours. The therapeutic implications of molecular subtyping to match appropriate therapies and the appreciation of the use of up to date radiotherapy techniques will be explored.